Perceived Stress and Low-Back Pain Among Healthcare Workers: A Multi-Center Prospective Cohort Study - Vinstrup, Jonas; Jakobsen, Markus D.; Andersen, Lars L. (Frontiers in Public Health, 2020)
Objective: This study aimed to investigate the association between perceived stress and odds of low-back pain (LBP) in a population of Danish healthcare workers. Methods: Utilizing a prospective cohort design with 1-year follow-up, a total of 1,944 healthcare workers from 389 departments at 19 hospitals responded to questionnaires containing items related to lifestyle, health, and working environment. Using Cohen's Perceived Stress Scale, associations between baseline stress levels and LBP intensity (0–10 scale) at follow-up were modeled using cumulative logistic regression, accounting for clustering at the department level and adjusting for age, sex, baseline intensity of LBP, education, seniority, number of daily patient transfers, psychosocial work environment, and lifestyle factors. Results: For the entire population, moderate and high stress (reference: low stress) at baseline increased the odds of LBP at 1-year follow-up with odds ratios (ORs) of 1.39 (95% CI 1.13–1.71) and 1.99 (95% CI 1.49–2.66), respectively. Sensitivity analyses among female nurses showed similar results [i.e., OR 1.40 (95% CI 1.08–1.80) and OR 2.08 (95% CI 1.44–3.00) for moderate and high stress, respectively], while only high stress significantly increased the odds among those without LBP at baseline. Conclusions: Psychological stress increases the odds of LBP among healthcare workers. Identifying and diminishing work-related psychosocial stressors should be included in strategies that aim to prevent musculoskeletal disorders in this population.